Understanding the Dynamics of Human Trafficking (Asia Pacific Journal of Social and Behavioral Sciences, 2015)
This study looked into the dynamics of human trafficking. Descriptive research design and exploratory method were used in the study that aimed to examine the connections between countries of origin, destination, and transit. The underlying characteristics of countries with high reported cases of human trafficking both in places of origin and destination were also scrutinized. The data were gathered from the Global Trafficking in Persons Report in 2009 through data mining. The countries with reported high cases of human trafficking were Armenia, Russia, Belarus, and the United States. The economic well-being, graft and corruption, and political stability were considered as contributing factors that facilitated and encouraged human trafficking. The study also revealed the dynamics or movement of human trafficking in various levels.
Keywords: Dynamics, human trafficking, places of destinations, places of origin, supply-demand relationship, corruption